TASK-BASED LANGUAGE LEARNING AND TEACHING (ACTIONABLE PERSPECTIVE) OF FRENCH IN SECONDARY SCHOOLS IN KENYA - Lutiali, Leonorah; Bwire, Adhelheid; Ondigi, Samson (International Journal of Research -GRANTHAALAYAH, 2021)
The nature and extent to which tasks are used in quality writing using the Task-Based Learning and Teaching(TBLT) is important in acquisition of French language. According to the Kenya National Examination Council (KNEC) reports, performance in quality writing in French is poor maybe because teachers of French may be using TBLT only in teaching. The purpose of this study was to assess the Task-Based Language Learning and Teaching (Actionable Perspective) of French in secondary schools in Kenya. The objective was to establish the nature and extent of TBLT use. The study was carried out in Nairobi City County where eight (8) secondary school teachers of French in Form three and one hundred and twenty-four (124) Form three students formed the study sample. A quasi-experimental research design was used. The data collection instruments were; teachers’ and learners’ questionnaires and a lesson observation guide. These instruments for data collection were refined through a pilot study. Data was analyzed qualitatively and quantitatively using descriptive statistics (means, ranks, frequencies, percentages, standard deviation). It was presented in frequency tables and bar charts. The findings were that TBLT was not only being used in teaching and learning but also in assessment and choice of learning resources. The study recommended use of TBLT alongside other methods, review of text books in line with TBLT, inclusion of TBLT in the syllabus at the teacher-training colleges/universities and mentorship programs in TBLT.